MON-LB44 Cushing’s Syndrome and Illegal Receptors - Poku, Caroline (J Endocr Soc, 2020)
Case presentation: A 48-year-old female with HTN presented to the endocrinology clinic for the evaluation of incidental bilateral adrenal masses noted on chest CT for dyspnea workup. At the time of the presentation, she reported generalized fatigue, significant weight gain in the past year and shortness of breath. Her physical exam was remarkable for central obesity. Lab work showed elevated cortisol after 1 mg dexamethasone suppression test x 2 and elevated 24- hour urine cortisol. Plasma free metanephrine levels and aldosterone/ renin ratio were normal. MRI abdomen was done and showed bilateral adrenal masses (left: 5.6 cm, right: 3.2 cm). Patient was diagnosed with Cushing’s syndrome secondary to primary bilateral adrenal hyperplasia and was referred to endocrine surgery who recommended unilateral adrenalectomy. The decision was made to remove the larger left side adrenal mass. On post-operative day one her am cortisol decreased to 2.1 and she was started on hydrocortisone 20 mg in the morning and 10 mg in the evening. Discussion: Primary bilateral adrenal hyperplasia is a rare cause (< 2 %) of endogenous Cushing’s syndrome, usually occurs in a bimodal age distribution, in childhood and in the fifth- sixth decades. Presentation is variable with most patients having no symptoms or subclinical Cushing’s. The theory is the larger nodule size corelates with the higher cortisol production. Studies have shown between 60-70% of cases has aberrant ectopic hormone receptors which leads to increased cortisol production not only from ACTH but also from other ligands such as serotonin and vasopressin. Aberrant receptor testing examines whether cortisol or other steroid production increases in response to either physiologic or pharmacologic stimulus. Multiple genetic mutations have been associated, the most frequent is mutations in the Armadillo repeat- containing 5 gene identified in 2013. Treatment can either be medical or surgical. Medical therapy can be initiated if testing for an aberrant receptor is positive. In recent years there has been a trend towards doing unilateral adrenalectomy instead of bilateral, with initial remission of symptoms reported in about 84% of cases after unilateral adrenalectomy although there is a small risk of recurrence. Post operatively after unilateral adrenalectomy patients should be monitored for adrenal insufficiency. Our patient declined aberrant receptor testing and opted for surgery and is doing well post operatively. Conclusion: Primary bilateral adrenal hyperplasia is a rare cause of endogenous Cushing’s syndrome which can be treated either medically or surgically.